EVOLUTION OF EDUCATION CURRICULUM IN THE UNITED STATES FROM THE 19TH TO THE 21ST CENTURY - Jannah, Syakilatul; Setiawan, Veri (Satmata: Journal of Historical Education Studies, 2024)
This study aims to explore the evolution of the educational curriculum in the United States from the 19th to the 21st century, analyze the factors influencing these changes, and understand how the curriculum has adapted to meet the evolving needs of society. This research utilizes historical research methods, including heuristic, source criticism, interpretation, and historiography stages. Data were collected through literature reviews encompassing books, journal articles, policy documents, and official reports. Content analysis techniques were employed to identify key themes and patterns from the collected data. The findings indicate that the educational curriculum in the United States has undergone significant changes, from a focus on classical education and religious values in the 19th century, diversification of the curriculum in the 20th century in response to industrial needs and social changes, to the integration of technology and 21st-century skills in the 21st century. Each period reflects an adaptation to evolving social, economic, and technological demands. This study provides valuable insights into how educational curricula can adapt to changing times, aiding policymakers and educators worldwide in developing more inclusive, relevant, and future-ready educational systems. Understanding the historical evolution of the curriculum offers a deeper perspective on the role of education in shaping an inclusive and sustainable global society.